A Commentary: Education in Canada - Does Anyone Read Our Constitution? - Ron S Phillips (Brock University, 2019)
Education in Canada is generally considered to be within the exclusive domain of the thirteen provincial and territorial governments.  There are numerous statements or writings from politicians, textbook authors, federal and provincial governments, researchers, newspaper columnists, as well as education organizations that state unequivocally that education in Canada is the exclusive jurisdiction of the provinces and territories.  Some statements indicate that the federal government has no constitutional role in education.  Such misinformation and beliefs have had severe consequences for First Nations as Canadians absolve federal inaction in First Nations education because 'education is a provincial responsibility'.  However, education in Canada is the constitutional responsibility of both the federal and provincial/territorial governments.  This article will examine the federal government's constitutional responsibility in education, as well as the consequences of the misinformation.